Mitochondrial DNA haplogroups modulate the serum levels of biomarkers in patients with osteoarthritis. Issue 5 (23rd November 2009) - Rego-Pérez, I; Fernández-Moreno, M; Deberg, M; Pértega, S; Fenández-López, C; Oreiro, N; Henrotin, Y; Blanco, F J
Abstract : Objective: To analyse the influence of mitochondrial DNA (mtDNA) haplogroups on serum levels of molecular biomarkers in patients with osteoarthritis (OA). Methods: Serum levels of molecular biomarkers of cartilage metabolism (collagen type II markers: C-terminal neoepitope generated by the collagenase-mediated cleavage of collagen type II triple helix (C2C), collagen type II (Coll2-1, and its nitrated form, Coll2-1NO2 ), procollagen type II (CPII)), synovial metabolism (hyaluronic acid (HA)) and cartilage and synovial turnover (cartilage glycoprotein 39 (YKL-40)) were analysed in 73 patients with OA and 77 healthy controls using ELISAs. All participants had been previously genotyped for the mtDNA haplogroups J, U and H. Non-parametric and multivariate analysis were performed to test the effects of the clinical variables, including gender, age, smoking status, diagnosis, mtDNA haplogroups and radiological Kellgren and Lawrence (K/L) grade on the serum levels of the molecular markers. Results: Non-parametric analysis found increased serum levels of HA in patients with OA, while the values for C2C and the C2C/CPII ratio were significantly higher in the healthy controls. A multiple regression analysis showed a relationship between the mtDNA haplogroups and serum levels of the typical collagen type II markers. Carriers of the mtDNA haplogroup H had higher levels while carriers of the mtDNA haplogroup J showed lower levels. Statistically significant interactions between mtDNA haplogroups and diagnosis and between mtDNA haplogroups and radiological K/L grade in the serum levels of molecular markers were also found. Conclusion: A new role for mtDNA haplogroups emerges from this work. The results suggest that the mtDNA haplogroups interact significantly with the serum levels of OA-related molecular markers, suggesting the possibility of their use as a complementary assay with these molecular markers.